Marketing strategies of agricultural producers in objective one Greek regions: the factors affecting the selection of marketing channels of sheep and goat producers - Tsourgiannis L.; Errington A.; Eddison J. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
This paper aims to examine the factors affecting the choice of marketing channel by sheep and goat farmers in the Region of East Macedonia and Thrace (EMTh) in Greece relative to the distribution of their livestock and milk produce. The survey was conducted in the spring of 2002 whereby the sample consisted of 343 sheep and goat farmers in the Region of EMTh in Greece. The effective response rate was 92%. A chi-square analysis was employed to assess the association between farm/farmer characteristics and the selection of a marketing channel. The Kruskal-Wallis non-parametric test was used to identify the relationship between each of the factors affecting the choice of marketing channel and the selection of a particular channel. Four categories of milk marketing channels and four categories of livestock marketing channels were identified. Many factors were found to be associated with the selection of milk marketing channel, including milk price, loyalty, speed of payment, degree of isolation, farm area, size of flock, volume of production, farmer's age and debt level. Factors such as livestock price, loyalty, capability of buyer to purchase large quantities of livestock/meat, speed of payment, personal relationships, size of flock and number of slaughtered lambs are associated with selection of a livestock marketing channel.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)